Nyadranan: A Medium for Local Economic Resilience and Cultural Preservation in the Rural of Nganjuk, East Java - Yudha, Ana Toni Roby Candra; Arianti, Bella Dahniar; Sherawali, Sherawali (Faculty of Sharia and Islamic Economic, Universtas Annuqayah, 2026)
Nowadays, local tourism continues to be excellent since the government declared it safe from COVID 19, especially Nganjuk, in East Java. The region known as the 'City of Winds' has quite a lot of tourism potential that continues to be maintained, such as natural tourism, traditional tourism, and educational tourism that has been maintained for generations. Nyadranan, which is a village clean-up activity, is one of the traditional tourism that has survived until this era of society 5.0. Its position that still exists aims to preserve local culture and at the same time utilise it as a source of economic empowerment. This study was conducted in a phenomenological manner, in which the authors were technically involved in the life of the village community who routinely organised 'Nyadranan' every year. This study can be observed with the findings that there are entertainment and economic activities that intersect with social, cultural, economic and psychological aspects, including dance, puppetry, and ludruk art which actually have a multiplier effect on the emergence of seasonal business opportunities. Based on these findings, it is hoped that at least the village government and even the city district, can facilitate this tradition to become bigger on an economic and cultural scale, with the preservation of other traditional tourism.